Novel Fiducial Fiber Scanning Measurement Method Based on a Polar Coordinate System for LAMOST. (1st March 2023) - Zhang, Zhen; Chen, Guifeng; Liu, Wenqi; Zhu, Mengjie; Wang, Menghao; Gu, Yonggang; Zhai, Chao
Abstract: The multiobject fiber-fed spectrograph is the core scientific instrument for large-scale spectroscopic surveys. For closed-loop control of fiber positioning, fiber metrology systems are implemented in numerous fiber-fed spectrographs. The position accuracy of the fiducial fiber in the focal plate directly affects the performance of the fiber metrology system. However, there are currently no suitable methods and devices for measuring the fiducial fibers with high accuracy in the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST). To solve this problem, this study proposed a novel online scanning measurement method for fiducial fibers in which a scanning camera was set up in front of the focal plate, and the rotation and translation movements of the focal plate were combined to set a polar coordinate measurement system. First, the pole and polar axis of the polar coordinate frame were determined, and the compensation values of the polar radius and angle of the polar coordinate of the fiducial fibers were solved in the field of view of the scanning camera. A prototype measurement platform was set up to verify the feasibility and scientific validity of the method. Experiment results show that the polar radius accuracy of the proposed method met the measurement requirements. The X – Y measurement accuracy can be further improved when a higher-precision rotary stage is adopted. Thus, the difficulties in online accurate measurement for fiducial fibers can be tackled by the proposed method with good operability in LAMOST.